Social and individual factors mediate chimpanzee vocal ontogeny - Soldati, Adrian;; Fedurek, Pawel;; Dezecache, Guillaume ;; Muhumuza, Geresomu;; Hobaiter, Catherine;; Zuberbühler, Klaus;; Call, Josep (Nature Publishing Group UK, 2025)
Abstract Human language develops in social interactions. In other ape species, the role of social learning in vocal ontogeny can be typically underappreciated, mainly because it has received little empirical attention. Here, we examine the development of pant hoot vocalisations during vocal exchanges in immature wild chimpanzees (Pan troglodytes schweinfurthii) of the Sonso community of the Budongo Forest, Uganda. We investigated how maternal gregariousness, age, sex, and social context are associated with behavioural and vocal responses to other group members’ calls. We show that the older sons of gregarious mothers are more likely to orient their attention, respond vocally to the calls of others, and are overall more exposed to others’ calls compared to other immature individuals. This effect is strongest in the presence of adult males and when their mothers also respond vocally, suggesting that chimpanzee vocal development is enhanced by social and vocal exposure. Our findings are consistent with a more flexible and socially mediated chimpanzee vocal ontogeny than previously assumed and show some parallels with animal vocal learners and children language acquisition.